1992
DOI: 10.1002/jnr.490310325
|View full text |Cite
|
Sign up to set email alerts
|

Transient, cyclic changes in mouse visual cell gene products during the light‐dark cycle

Abstract: Temporal and spatial changes in the cellular and subcellular concentrations of photoreceptor cell gene products appear to be important features of phototransduction in rod photoreceptor cells. The time course of the rapid, light-dependent movement of S-antigen (S-Ag) (48k; Arrestin) from the inner segments to the outer segments was analyzed using polyclonal and monoclonal antibodies. The concentrations of mRNA change about threefold for rhodopsin and about sixfold for S-Ag in cyclic, independent modes during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 21 publications
6
43
0
Order By: Relevance
“…1, 15 min, 60 min light). This pattern of arrestin immunoreactivity and the time course of arrestin translocation were similar to previous reports (Philp et al, 1987;Mangini and Pepperberg, 1988;Whelan and McGinnis, 1988;McGinnis et al, 1992).…”
Section: Light Causes Arrestin Translocation In the Absence Of Rhodopsupporting
confidence: 92%
See 2 more Smart Citations
“…1, 15 min, 60 min light). This pattern of arrestin immunoreactivity and the time course of arrestin translocation were similar to previous reports (Philp et al, 1987;Mangini and Pepperberg, 1988;Whelan and McGinnis, 1988;McGinnis et al, 1992).…”
Section: Light Causes Arrestin Translocation In the Absence Of Rhodopsupporting
confidence: 92%
“…Light triggers a massive movement of transducin to the rod inner segment in the opposite direction from arrestin (Brann and Cohen, 1987;Philp et al, 1987;Whelan and McGinnis, 1988;Organisciak et al, 1991;McGinnis et al, 1992;Sokolov et al, 2002). We showed that arrestin translocation was unaffected in the absence of Tr ␣ .…”
Section: Arrestin and Transducin Translocation In Retinal Rods Are Inmentioning
confidence: 77%
See 1 more Smart Citation
“…9B. Arrestin was present predominantly in the inner segments of photoreceptors of dark-adapted retinas but was present only in the outer segment of light-adapted retinas, in agreement with previous reports (22). The translocation of arrestin between the inner and outer segments is quite evident; however, Src shows only differences in the intensity of reaction and not localization in response to light.…”
Section: Light-induced Tyrosine Phosphorylation Of Ros-supporting
confidence: 91%
“…The onset of rod arrestin gene transcription in mouse occurs before rod outer segment formation (27), whereas in the bovine retina, arrestin expression is concurrent with other genes involved in phototransduction (28). Transcription of arrestin also appears to be regulated by diurnal or circadian rhythms in certain species (29,30,31). However, the mechanisms that control arrestin expression are not understood.…”
mentioning
confidence: 99%